The Influence of Fundamental Factors on Stock Returns with Exchange Rate as Moderation Variable - Anggraini, Reny Dwi; Wijayanto, Andhi (Universitas Negeri Semarang, 2021)
Return are one of the motivators to invest in financial asset in the capital market. Investors used fundamental factor as a signal to gain maksimal return. The aims of the study are to determine the effect of fundamental factor on stock return with exchange rate as a moderating variable. Fundamental factor is measured by the ratio of Return on Assets, Debt to Equity Ratio, and Current Ratio. The sample of this study of 20 companies listed on LQ45 index in Indonesian Stock Exchange (IDX) selected using the purposive sampling method, with 120 observations during the 2015-2020 period. Methode of data analysis using multiple linier regression analysis and moderated regression analysis (MRA) with the application of Eviews 9. The results show that Return on Assets have a significant positive effect on the stock returns, while the Debt to Equity Ratio and Current Ratio has no significant effect. MRA results indicate that exchange rate can streng the influence of Return on Assets and Debt to Equity Ratio, and weaken Current Ratio on the stock returns.